PENERAPAN PENDIDIKAN MENTAL ISLAMI DI LINGKUNGAN NARAPIDA POLDA SUMATERA UTARA - Saiful Akhyar Lubis; Abdurrahman Abdurrahman; Mayurida Mayurida (JP : JURNAL PENDIDIKAN, 2020)
Abstract: This research aims to knowing the mentality of a suspect who is undergoing a criminal legal process at the investigation level. Second, knowing the mental health development of suspects who are undergoing legal procee-dings at the investigation level. Thrid, knowing the Urgency of guidance and counseling for suspects who are undergoing criminal legal proceedings at the investigation level. This type of research is qualitative research with a case study approach. There are also informants in this study are the suspects, investigators, lawyers, former suspects; data collected by the method of observation, interviews and documentation. The results obtained in this study are that people who undergo criminal proceedings at the investigation level experience mental and psychological disturbances and pressures, and require counseling guidance but there are no rules in the Republic of Indonesia that govern the permissibility and guidance and counseling. Against suspects who carry out criminal legal proceedings at the investigation level, while for assistance in terms of legal proceedings, the state prepares lawyers (lawyers) who are prodeo for those who are able to pay, so the state invites to appoint its own legal advisors (lawyers). The mental health of suspects who undergo criminal proceedings at the investigation level affects the resolution of problems that occur at the investigation levelKeyword: Mentally, Education and Suspect